Application of a holistic approach in learning Indonesian Language for elementary school students - Bahari, Priya Kusuma; Kusumaningrum, Shirly Rizki; Mardhatillah; Mashfufah, Aynin; Hanafi, Yusuf (Universitas Kanjuruhan Malang, 2025)
The purpose of this study is to provide an in-depth description of the application of a holistic approach in Indonesian language learning and its benefits for elementary school students. The research method used is qualitative with a qualitative descriptive design. Data were collected through unstructured interviews with teachers, participatory observation in the classroom, and documentation, then analyzed using thematic analysis techniques. The results showed that the holistic approach, with the principles of Connectedness, Wholeness, and Being, can integrate language skills with the context of students' lives, involve various senses and emotions, and provide opportunities for exploration of interests and talents. This approach has the potential to improve students' understanding of the subject matter, develop critical thinking skills, creativity and strong character, and create a fun, democratic and humanist learning atmosphere.